1999
DOI: 10.1111/j.1574-6968.1999.tb13375.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of theAcinetobacter baumanniiFur regulator: cloning and sequencing of thefurhomolog gene

Abstract: Growth kinetics, siderophore activity and iron-regulated bacterial proteins of Acinetobacter baumannii BM2580 were studied in iron-restricted and iron-supplemented chemically defined media. Iron-regulated outer membrane proteins of 75 kDa and 80 kDa were expressed under iron-restricted conditions. Cloning and sequencing of the complete iron-uptake regulatory (fur) gene from A. baumannii BM2580 is reported for the first time. This gene is preceded by a single autoregulated promoter whose -10 region overlaps the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 19 publications
(27 reference statements)
0
15
0
Order By: Relevance
“…These include: (i) the TetR and LysR proteins AdeN (ABUW_1731) and AdeL (ABUW_1338) [19]; (ii) two members of the Fur family, Fur (ABUW_3033) and Zur (ABUW_3741) [21, 22, 24]; and (iii) the MerR-like protein SoxR (ABUW_2555) [23]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include: (i) the TetR and LysR proteins AdeN (ABUW_1731) and AdeL (ABUW_1338) [19]; (ii) two members of the Fur family, Fur (ABUW_3033) and Zur (ABUW_3741) [21, 22, 24]; and (iii) the MerR-like protein SoxR (ABUW_2555) [23]. …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the ferric-uptake regulator (Fur) has been described as controlling expression of genes involved in siderophore production [21, 22]. A fourth TF, SoxR, is a MerR-like regulator governing transcription of the AbuO outer-membrane protein, which is important for resistance to osmotic and oxidative stress [23].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the moderate inhibitory, but non-lethal effect of 200 μM DIP, this concentration was chosen to study transcriptional changes under iron limitation. Preliminary qRT-PCR was performed to confirm transcriptional adaptation in response to iron limitation by assaying the level of transcription of the ferric uptake regulator (FUR), which is known for auto-up-regulation when iron is limited [26]. A. baumannii grown in the presence of 200 μM DIP expressed FUR at levels increased more than 2-fold compared to cells grown under iron replete conditions (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…These observations suggest that Ab-mediated iron acquisition may have an important role in the pathogenesis of A. baumannii infections. Moreover, Daniel et al (1999) reported that A. baumannii also possesses a Fur protein 63 % identical to that of Escherichia coli. In accordance with this, several Fur-target genes have recently been identified in this species (Echenique et al, 2001;Dorsey et al, 2003).…”
Section: Introductionmentioning
confidence: 99%